2021
DOI: 10.3390/membranes11040235
|View full text |Cite
|
Sign up to set email alerts
|

Green Approaches for Sustainable Development of Liquid Separation Membrane

Abstract: Water constitutes one of the basic necessities of life. Around 71% of the Earth is covered by water, however, not all of it is readily available as fresh water for daily consumption. Fresh water scarcity is a chronic issue which poses a threat to all living things on Earth. Seawater, as a natural resource abundantly available all around the world, is a potential water source to fulfil the increasing water demand. Climate-independent seawater desalination has been touted as a crucial alternative to provide fres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 159 publications
0
20
0
Order By: Relevance
“…Fortunately, some researches indicate that it is completely possible to achieve these goals with greener solvents, not yet now but very soon. 262 Moreover, the treatment and recycling of the used organic solvents may be a viable approach to reduce waste.…”
Section: Solid Membranes For Chiral Resolutionmentioning
confidence: 99%
“…Fortunately, some researches indicate that it is completely possible to achieve these goals with greener solvents, not yet now but very soon. 262 Moreover, the treatment and recycling of the used organic solvents may be a viable approach to reduce waste.…”
Section: Solid Membranes For Chiral Resolutionmentioning
confidence: 99%
“…While the reutilization of bio-based waste as polymeric raw material is expected to bring down the unfavourable effects of engineering polymers to certain extent, the use of green solvent in the dissolution of solid waste-derived raw material during membrane fabrication is also imperative to maximize the process sustainability. A number of studies have demonstrated the feasibility of green solvent or the less toxic solvent in the preparation of polymer dope solution [169]. It is worth noting that, although IL has been well recognized as a versatile green solvent due to its high dissolution capacity and recyclability, the current production cost of ionic liquid is still the major hindrance for its commercial viability.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…These solvents are deadly to both humans and the environment [2] . Most of these solvents are reported to cause eye, skin and respiratory irritation [3] . They affect aquatic life and are suspected to be carcinogenic.…”
Section: Introductionmentioning
confidence: 99%
“…They affect aquatic life and are suspected to be carcinogenic. Many of them are known to cause reproductive disorders in humans [3] . N‐Methyl‐2‐Pyrrolidone (NMP) happens to be the most used solvent for membrane preparation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation